2017
DOI: 10.1055/s-0043-107031
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Guided Isolation of Iridoids and Phenylpropanoids from Aerial Parts of Lamium album and Their Anti-inflammatory Activity in Human Neutrophils

Abstract: In traditional medicine, flowers and aerial parts of are assigned by their anti-inflammatory, antiseptic, and mucolytic activities, and are used in chronic bronchitis and pharyngitis as well as skin, vaginal, and cervical inflammation.The aim of the present study was to compare effects of ethanolic extracts prepared from flowers and aerial parts of on selected functions of human neutrophils, which are involved in an inflammatory response. In order to identify the compounds engaged in the anti-inflammatory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
0
25
1
Order By: Relevance
“…Further investigations indicated that, although tiliroside inhibits the phosphorylation of MAPK/JNK and MAPK/p38 proteins, it still demonstrates no significant inhibition of the phosphorylation of MAPK/ERK or the degradation of IκB‐α (Jin et al., ). Czerwińska, Świerczewska, Woźniak, and Kiss () reported that tiliroside at a concentration of 25 μM could effectively inhibit IL‐8, TNF‐α, and ROS generation in polymorphonuclear leukocytes; however, this activity was lower than those of the reference compounds dexamethasone and oleocanthal.…”
Section: Biological Activities Of Tilirosidementioning
confidence: 99%
“…Further investigations indicated that, although tiliroside inhibits the phosphorylation of MAPK/JNK and MAPK/p38 proteins, it still demonstrates no significant inhibition of the phosphorylation of MAPK/ERK or the degradation of IκB‐α (Jin et al., ). Czerwińska, Świerczewska, Woźniak, and Kiss () reported that tiliroside at a concentration of 25 μM could effectively inhibit IL‐8, TNF‐α, and ROS generation in polymorphonuclear leukocytes; however, this activity was lower than those of the reference compounds dexamethasone and oleocanthal.…”
Section: Biological Activities Of Tilirosidementioning
confidence: 99%
“…Furthermore, the R 2 values obtained between the total phenol content and ABTS assay, as well as between flavonoids and the ABTS were 1.00 and 0.987, respectively. [1,2,5,6,[9][10][11] 13.83% Oxygenated monoterpenes [14,[17][18][19] 6.99% Sesquiterpene hydrocarbons [25,27,29,30,33,34,35] 6.36%…”
Section: Correlation Between Antioxidant Capacity and The Total Phenomentioning
confidence: 99%
“…These species exhibit multiple biological actions, including antimicrobial [6], antifungal [7], antioxidant [8][9][10][11][12], antiinflammatory and nociceptive [13] as well as anticancer [14,15] activities. Literature data point to the presence of different classes of chemical compounds: including ecdysone and phenylpropanoid glucosides [16], iridoid glucosides [17,18] and oligosaccharides [19]. Interest in the medicinal properties of these plants has led to intensive phytochemical and pharmacological investigations [5,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In Spain its root is used in wound healing and its flower to eliminate severe diarrhea. Studies on the L. album aerial parts extract in order to evaluate its pharmacological properties have been done and showed the following properties in different condition: purify the blood, lowers blood sugar, treats anemia and mild diarrhea, stomachulcers, kidneystones, rheumatism, varicoseveins, sore, insomnia, dandruff, depression, regulate menstruation, induce hair growth, reduce joints pain and detoxifies the body 5 . Other effects are in preventing menstrual disorders, abdominal inflammation, musculoskeletal diseases 15 antioxidant properties 16 .…”
Section: Fig 1: Lamium Albummentioning
confidence: 99%
“…Superoxide have useful role in regulating cell growth and intercellular messages. Plants with antioxidant properties can also have anti-inflammatory, anti-depressant, and so on effects 5 .…”
mentioning
confidence: 99%